Understanding of the characteristics of fibroblasts in ischemic cardiomyopathy using single-nucleus RNA sequencing - Qianyuan Zhang; Ziwen Cai; Yongqiao Zhang (Scientific Reports)
Abstract Fibroblasts play a crucial role in the development and progression of heart failure in many heart-related diseases. However, the contributions of fibroblast and its subtypes to the pathogenesis of ischemic cardiomyopathy (ICM) remain unclear. In this study, we analyzed single-nucleus RNA sequencing data from cardiac tissues of seven ICM patients with heart failure and eight control subjects. Our findings indicate that, compared to controls, fibroblasts from ICM patients exhibit dysregulation of genes associated with cell-substrate adhesion and matrix or collagen fibril organization. We further identified five fibroblast subtypes, designated as FB1 through FB5, with FB3 exhibiting the highest frequency in ICM. Pseudotime trajectory analysis further revealed an evolutionary progression of fibroblasts from FB1/FB2 toward FB3. Differential gene expression analysis of FB3 highlighted several subtype-specific genes, such as NTM, THBS4, NRK, NAV2, and PLA2G5. Furthermore, intercellular interaction analysis revealed that FB3 exhibits weakened interactions with other cells under ICM. Specifically, signaling interactions involving ANGPTL and COLLAGEN are reduced, whereas pathways mediated by THBS, NRXN, and APP are strengthened. These results provide valuable insights into the fibroblast microenvironment and elucidate the pathological mechanisms underlying ICM, laying a theoretical foundation for the identification of novel therapeutic targets.